THE OBLIGATORINESS OF REGISTRATION OF ENTERPRISES PROVIDERS OF SERVICES IN PHYSICAL ACTIVITY AND RELATED IN REGIONAL COUNCIL OF PHYSICAL EDUCATION 12TH REGION CREF12/PE-AL IN MACEIÓ - AL: AN EXPEREINCE REPORT IN ACTIONS OF SURVEILLANCE (Fiep Bulletin - online, 2014)
Justification: Gyms, weight training and services companies and related physical activities are part of a growing market and occupying a large proportion of the health and aesthetics in Brazil. Despite the demand for an ideal body, these establishments have responsibility for the lives of their users and comply with the regulations that are imposed, ensuring quality and safety of services provided to the population. Objectives: Check the current adequacy of the regularity companies operating in the city of Maceió, Alagoas State during the period September 2011 to September 2013. Methods: This is a study of data analysis done on the result of the actions of guidance and supervision of the Regional Council of Physical Education of the 12th Region CREF12/PE-AL. Results: It was observed that within two years there has been significant increase in the number of companies that were regulated. Conclusion: However it is clear that approximately 33.95% of the companies are still illegal, which reinforces the need for action in partnership with all enforcement agencies to ensure the safety of users.
Keywords: Regularization; Health; Surveillance